Investigating inefficiencies in the German rental housing market: The impact of disclosing total costs on energy efficiency appreciation - Lisa Sieger (University of Duisburg-Essen, House of Energy Markets & Finance (HEMF), 2023)
Energy efficiency and renewable energy are key pillars of the energy transition that is high on the political agenda of governments in face of the climate crisis. Germany, however, is underperforming in its emissions reduction goals. There is still room for improvement, especially in the building sector - but this is often associated with high upfront investments. There is evidence that the market for energy efficiency in the German rental housing market is inefficient, resulting in underinvestment. To investigate these inefficiencies, this study estimates a hedonic pricing model combined with a total-cost-of-use perspective based on the observation of warm rents for a sample of 3,903,473 rental offers from 2014 to 2021. In a "perfect world", the effect of the energy performance score given in energy performance certificates as an indicator of energy consumption or demand, respectively, is expected to be zero, as corresponding costs are already included in the warm rent. If the coefficient is significantly different from zero, it can be interpreted as measure for inefficiencies. The study further investigates whether disclosing heating costs in real estate advertisements could lead to a better appreciation of energy efficiency in the rental market and thus contribute to closing the information gap. Results show that the market for energy efficiency is indeed inefficient; however, the disclosure of full information can help to overcome these inefficiencies. These results lead to several important policy implications.
Keywords: C31; Q40; R21; R31; 330; energy efficiency; rental housing market; information asymmetry; hedonic pricing